Cation nutrient reserves decline markedly under intensive cropping of Pampas Mollisols - Larrea, Gaston Emiliano; Wyngaard, Nicolás; Eyherabide, Mercedes; Reussi Calvo, Nahuel Ignacio; Puricelli, Marino Marcelo; Barbieri, Pablo; Angelini, Hernán Pablo; Salvagiotti, Fernando; Sainz Rozas, Hernan Rene (Elsevier, 2023)
The availability of exchangeable cationic nutrients in soils, such as calcium (Cae), magnesium (Mge), and potassium (Ke), is vital for crops growth and development. However, the concentration of these nutrients can be diminished by land use and management practices. The objectives of this study were i) to determine the concentration of Cae, Mge, and Ke in uncropped soils or soils under continuous agriculture, ii) to determine the Cae, Mge and Ke decrease rate due to agriculture (dCae, dMge, and dKe, respectively), iii) to evaluate the relative contribution of edaphoclimatic and farming variables on dCae, dMge, and dKe, and iv) to evaluate the spatial variability of Cae, Mge, and Ke. Surface soil samples (0–20 cm layer) were taken in 2011 and 2018 at geo-referenced sampling locations within 507 agricultural production fields (AGR2011 and AGR2018) from the Argentinean Pampas region (PR). Additionally, surface soil samples were taken from areas under gramineous vegetation that had never been cropped at each sampling point. Path analysis explained 58, 42, and 56 % of the variability on dCae, dMge and dKe between 2011 and 2018, respectively. The main factors determining the depletion of these nutrients were the soybean relative harvested area for dCae, magnesium concentration in 2011 for dMge, and rainfall for dKe. The spatial variation of Cae, Mge, and Ke increased with the history of agricultural use of soils, particularly in the case of Ke and Mge. If the depletion of exchangeable cationic nutrients in the PR continues at current rates, their deficiencies for the main crops could become evident in the medium/short term, depending on the area. For this reason, it is necessary to continue surveying the evolution of soil Cae, Mge and Ke over time in the PR and other areas in the world with similar edaphoclimatic conditions.